Mechanism of Wuzhuyu decoction on alcohol-induced gastric ulcers using integrated network analysis and metabolomics - Wang, Xin; Chen, Lisheng; Chang, Lei; He, Yong; He, Tingting; Wang, Ruilin; Wei, Shizhang; Jing, Manyi; Zhou, Xuelin; Li, Haotian; Zhao, Yanling (Frontiers in Pharmacology, 2024)
Background: Gastric ulcers (GUs) are prevalent digestive disorders worldwide. Wuzhuyu Decoction (WZYT) is a traditional Chinese medicine that has been employed for centuries to alleviate digestive ailments like indigestion and vomiting. This study aims to explore the potential effects and underlying mechanisms of WZYT on alcohol induced gastric ulcer treatment. Methods: We employed macroscopic assessment to evaluate the gastric ulcer index (UI), while the enzyme-linked immunosorbent assay (ELISA) was utilized for detecting biochemical indicators. Pathological tissue analysis involved hematoxylin-eosin (H&E) staining and Periodic Acid-Schiff (PAS) staining to assess gastric tissue damage. Additionally, the integration of network analysis and metabolomics facilitated the prediction of potential targets. Validation was conducted using Western blotting. Results: The research revealed that WZYT treatment significantly reduced the gastric ulcer index (UI) and regulation of alcohol-induced biochemical indicators levels. Additionally, improvements were observed in pathological tissue. Network analysis results indicated that 62 compounds contained in WZYT modulate alcohol-induced gastric ulcers by regulating 183 genes. The serum metabolomics indicated significant changes in the content of 19 metabolites after WZYT treatment. Two pivotal targets, heme oxygenase 1 (HMOX1) and albumin (ALB), are believed to assume a significant role in the treatment of gastric ulcers by the construction of “compounds-target-metabolite” networks. Western blot analysis confirmed that WZYT has the capacity to elevate the expression of HMOX1 and ALB targets. Conclusion: The integration of network analysis and metabolomics provides a scientific basis to propel the clinical use of WZYT for GUs. Our study provides a theoretical basis for the use of Wuzhuyu decoction in the treatment of gastric ulcers.